Determination of the Percentage Ca(OH)2 Lime Stabilization Material for Weathered Clay Shale as Road Subgrade on Serang – Panimbang Toll Road Section III STA 57+200 - Sormin, Prince Joy; Satrya, Trihanyndio Rendy; Maulana, Mahendra Andiek; Supriyo, Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Clay shale consists of thin, layered formations with irregular fractions, highly smooth, and easily separable along the layer planes. If Clay shale is exposed to sunlight, air, and water for a relatively short period, it will undergo weathering. The construction of the Serang - Panimbang Toll Road Section III is carried out by cutting the soil according to the planned contours. After the cutting process, the subgrade material undergoes a change in its characteristic properties and mechanics because the subgrade soil is Clay shale material that has weathered, commonly referred to as